Relationships between the Salivary Microbial Composition and Gastrointestinal Diseases - Norouzpour, Asal; Dabiri, Hossein; Gholam-Mostafaei, Fahimeh Sadat; Rostami Nejad, Mohammad (Applied Food Biotechnology, 2022)
Abstract Background and Objective: Salivary microbiota, including bacteria shed from oral surfaces, is individualized, temporally stable and affected by the environmental factors such as diet, lifestyle and oral hygiene. Salivary microbiota is nonpathogenic and commensal; however, if microbiota colonizes into the intestines, they could alter gastrointestinal microbiota and result in development of several chronic inflammatory diseases, foremost autoimmune diseases and gastrointestinal cancers. There are few studies that assessed salivary microbiota in autoimmune gastrointestinal disorders. This may help researchers find novel personalized therapeutic approaches for the gastrointestinal diseases. Therefore, the aim of this review was to discuss alterations of salivary microbiota composition in gastrointestinal disease progress, including celiac disease, inflammatory bowel disease and gastrointestinal cancers. Results and Conclusion: This study suggested that oral microbiota composition is linked to chronic inflammatory diseases by changing the immune system responses through increasing the production of inflammatory cytokines and mediators. Investigation of saliva microbiota is becoming an important part of diagnosing gastrointestinal diseases and changes in the composition of oral microbiota can predict risks of disorder progression in high-risk individuals. Conflict of interest: The authors declare no conflict of interest.